Application and Exploration of Biosensors for Cancer Liquid Biopsy and Artificial Intelligence-Assisted Data Analysis - Zhang Tongrui (MATEC Web of Conferences)
Cancer is one of the diseases with the highest mortality rate in the world, and its early diagnosis and precise treatment have always been the focus of medical research. Traditional detection technology has limitations such as trauma and difficulty in dynamic monitoring, while biosensors combined with liquid biopsy as an emerging non-invasive detection technology can detect tumor-related markers in body fluids and convert them into quantifiable data through biosensors. However, liquid biopsy still faces challenges such as low marker concentration, weak signals, and complex data analysis. Therefore, it is necessary to combine high- sensitivity detection technology with intelligent data processing methods to improve its accuracy and clinical application value. This article will focus on the mechanism of biosensors in detecting tumor markers and the signal conversion process and provide a new path for cancer screening and detection with the assistance of artificial intelligence, which has a positive effect on breaking through the limitations of traditional detection methods.